Growth and wood yielding of Cedrela odorata l. and Tabebuia donnell-smithii Rose in San José Chacalapa, Pochutla, Oaxaca - Galán Larrea, Rolando; de los Santos Posadas, Héctor Manuel; Valdez Hernández, Juan Ignacio (Instituto de Ecología, A.C., 2016)
An explicit growth and yield system (GYS) was fitted to data from re-measured plots of Cedrela odorata (spanish cedar) and Tabebuia donnell-smithii planted at the Oaxaca’s coastal region. As a first stage, a total and merchantable volume system at tree level was fitted based on non-destructive sampling scheme. Afterwards a GYS was fitted using seemingly unrelated regression to achieve full compatibility among prediction and projection models.